Return, reliability and risk as a proactive set of concepts in developing an efficient integration strategy of companies - Rutkauskas, Aleksandras Vytautas; Ostapenko, Aleksandr (Journal of Business Economics and Management, 2016)
For companies that cannot boast about the abundance of resources available for development, it is particularly important to focus their efforts on the optimum use of such resources and to ensure the reliability of change in the development process to counterbalance the potential losses caused by uncertainty and risk. The article explores the theoretical substantiation for the integral management system of processes covered by the concepts of efficiency, reliability and risk of development. Also, it looks at the practical application of the system through the examination of a specific situation by employing analytical possibilities of a stochastic network. It should also be noted that the concepts of efficiency, reliability and risk are used not only in the assessment of the key development processes of a company but also in the deliberation of the real formation of input as well as its transformation into output results. To formulate and solve the management problems of the complex system, a number of methods were used, namely, the stochastic recording of the aims, the existing restrictions and the stochastic optimisation.